Християнський аспект формування міжнародних відносин в епоху Середньовіччя - Горбач, Олександр (Видавницво Львівської політехніки, 2014)
Досліджено історію розвитку міжнародних відносин в епоху Середньовіччя. Доведено, що у період епохи Середньовіччя міжнародні відносини сформувалися як певна система поглядів. Проаналізовано тенденції розвитку міжнародної політики щодо поєднання нових форм, способів координування політичної теорії та практики, появи дипломатії як основного засобу реалізації зовнішньої політики. In the history of world nations vast experience of international political relations has been accumulated, without which future comprehensive socio-political development of mankind is impossible. Developing the strategy and tactics of the state foreign policy, prominent thinkers, political leaders and political scientists formulated the basic principles and the principles of international relations. Practical application of these principles and guidelines sometimes led the states to political success, and sometimes it was the beginning of their crash. The article proved that during the Middle Ages international relations emerged as a belief system which had its goal, the means of its achievement, motivated principles and also its content. The integral system analysis of the history of international relations of the Middle Ages was made, trends of the development of international policy in terms of combination of new forms were analysed, methods of coordinating the political theory and practice, the essence of which is the gradual change of overt aggression of the Ancient times into civilized diplomacy during the Middle Ages. Medieval papal Rome left new concepts in the political thought such as subordination of civilian authority to the universal spiritual one, the possibility to form higher supranational entities and building of a Christian civilization. The origin of the primary means of foreign policy, that is diplomacy, should be considered as the achievement of the medieval Byzantium. Scientific understanding of the history of international relations will have practical significance in the formulation and practical implementation of foreign policy, and can also serve as recommendations to public authorities and political organizations in the formation of tasks aimed at determining the foreign policy of our state vector.
Christian aspects of the formation of international relations in the Middle Ages
Keywords: християнство; міжнародні відносини; Середньовіччя; Григорій VІІ; Інокентій ІІІ; Візантія; Christianity; international relations; Middle Ages; Gregory VII; Innocent III; Byzantium